Effect of selenium on the course of a postoperative period after liver transplantation - M. Sh. Khubutia; S. V. Zhuravel; A. M. Talyzin; V. V. Kiselev; Ye. R. Dorofeyeva; N. K. Kuznetsova; A. V. Chzhao (Трансплантология (Москва))
Objective: to study the effect of selenium on the course of a postoperative period in patients after orthotopic liver transplantation (OLT).Subjects and methods. The prospective controlled randomized study enrolled 30 patients after OLT. Selenium (Selenase, Biosyn) was administered in Group 1 (n = 15) within 5 days operatively. The agent was not used in complex therapy in Group 2 (n = 15).Results. After OLT, the plasma levels of selenium were much more than the normal value. In Group 1, the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were significantly lower on day 3 after OLT and those of urea and creatinine significantly decreased by day 7. A significant difference was found in scores on day 7, as shown by the analysis of the patients' condition by the SOFA scale. The patients who needed venovenous hemodiafiltration (VVHDF) were more than in those who did not use selenium.Conclusion. Selenium levels considerably decrease after liver transplantation. Selenase has a hepatoprotective effect, alleviates the manifestations of a systemic inflammatory response, and reduces the frequency of VVHDF use.